2016
DOI: 10.1159/000447919
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal CFTR Suppresses MAPK/NF-κB to Promote Cutaneous Wound Healing

Abstract: Background: CFTR is implicated in cutaneous wound healing although the underlying mechanisms are not fully understood. In other cell types, CFTR is reported to regulate MAPK/ NF-κB signaling. We undertook the present study to explore a possible role of CFTR in regulating MAPK/NF-κB during cutaneous wound healing. Methods& Results: The splint-excisional and incisional wound healing models were used in CFTR mutant (DF508) mice. The cell-scratch model was used in a human keratinocyte line, HaCaT, in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…AWP has been reported as either recessive or dominant trait. It occurs in up to 84% of patients with CF, which is due to biallelic mutations in the CF transmembrane conductance regulator ( CFTR ) gene (Table ) and characterized by a classical diagnostic triad of chronic lung disease, exocrine pancreatic insufficiency and abnormally high salt concentration in the sweat. Sporadic AWP individuals, described as affected with non‐classic CF or without CF, were shown to carry monoallelic or biallelic mutations in the CFTR .…”
Section: Syndromic Palmoplantar Keratodermasmentioning
confidence: 99%
“…AWP has been reported as either recessive or dominant trait. It occurs in up to 84% of patients with CF, which is due to biallelic mutations in the CF transmembrane conductance regulator ( CFTR ) gene (Table ) and characterized by a classical diagnostic triad of chronic lung disease, exocrine pancreatic insufficiency and abnormally high salt concentration in the sweat. Sporadic AWP individuals, described as affected with non‐classic CF or without CF, were shown to carry monoallelic or biallelic mutations in the CFTR .…”
Section: Syndromic Palmoplantar Keratodermasmentioning
confidence: 99%
“…Various animal wound‐healing models have been successfully utilized to better understand the basic mechanisms of the acute wound‐healing process, and to some extent, its pathophysiology . The most commonly used animal models for wound healing, such as murine, rat, porcine and rabbit, are widely available and share important anatomical and physiological characteristics with the human wound‐healing process.…”
Section: “Pros and Cons”: Animal Vs Human Wound‐healing Modelsmentioning
confidence: 99%
“…SF has been shown to be promising as a wound dressing due to its excellent biocompatibility, biodegradability, and low immunogenicity [9,10]. When SF dressings cover a skin defect, the NF-kB signaling pathway can be stimulated to control the expression of vimentin, cyclin D1, vascular endothelial cell growth factor, and fibronectin [11][12][13][14], which regulate cell adhesion and proliferation [15] and enhance c-Jun protein expression and phosphorylation to promote wound healing [16]. The results of our previous studies have shown that three-dimensional SF scaffolds prepared by freeze-drying can guide the growth of capillaries, microvessels, and fibroblasts and promote the regeneration of dermal tissue [17][18][19].…”
Section: Introductionmentioning
confidence: 99%